Effect of auxiliary wire feeding on cold metal transfer directed energy deposition of stainless steel: A study on droplet transfer, formation characteristics, and microstructure - Yi Feng; Qiming Jiang; Ding Fan (Journal of Materials Research and Technology)
While traditional cold metal transfer direct energy deposition (T-CMT-DED) can be sped up by increasing the deposition current; this often negatively affects the deposited part's shape and microstructure due to increased heat input. To address this, we propose a novel approach: auxiliary wire feeding cold metal transfer direct energy deposition (AWF-CMT-DED). In this study, we analyzed the droplet transfer behavior, weld bead geometric characteristics, and stability of stainless steel printed utilizing both T-CMT-DED and AWF-CMT-DED. We observed that increasing the auxiliary wire feed speed led to a greater bead height while maintaining a constant bead width. When the auxiliary wire feed speed reached its upper limit for a given deposition current, the AWF-CMT-DED deposition rate was at least 1.46 times higher than that of T-CMT-DED at the same deposition current. Specifically, the AWF-CMT-DED mode, by reducing the molten pool's temperature gradient, facilitated the formation of fine grains, and the average grain size is 50.9 μm. Microstructural analysis indicated that the grain size decreased under the AWF-CMT-DED mode. In a word, this study illustrates that AWF-CMT-DED can achieve a higher deposition rate and lower heat input to the deposited layers, all while preserving high forming quality.